Transcriptional Regulation and Posttranslational Activity of the Betaine Transporter BetL in Listeria monocytogenes Are Controlled by Environmental Salinity - Sleator, Roy D. (American Society for Microbiology, 2003)
While the genetic elements contributing to the salinity tolerance of Listeria monocytogenes have been well characterized, the regulatory signals and responses (genetic and/or biochemical) that govern these mechanisms have yet to be elucidated. Encoded by betL, the first genetic element to be linked to listerial osmotolerance, the secondary betaine uptake system BetL is a member of the betaine-carnitine-choline transporter family. Preceded by consensus σ(A)- and σ(B)-dependent promoter sites, betL is constitutively expressed and transcriptionally up-regulated in response to salt stress. The nisin-controlled expression system was used to achieve salinity-independent, controlled betL expression in Listeria. In the absence of NaCl-activated transcriptional control, BetL activity was found to be a function of environmental salinity, showing optimal activity in buffer supplemented with 1 to 2% NaCl (osmolality, 417 to 719 mosmol/kg). In addition, BetL was activated rapidly (half-life, 2 min) in response to an osmotic upshift imposed by adding 2% NaCl to 50 mM potassium phosphate buffer.